2014
DOI: 10.1007/s00330-014-3249-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and variables associated with solitary pulmonary nodules in a routine clinic-based population: a cross-sectional study

Abstract: ObjectiveTo determine the prevalence of solitary pulmonary nodules (SPNs) in chest radiology studies and patient’s features associated with malignancy in a non-high-risk clinical population.MethodsPatients ≥35 years were referred for thoracic imaging in two hospitals (2010-2011). Eight radiologists determined the presence and characteristics of SPN. Selected variables were collected from radiological register and medical records. Observer agreement in the diagnosis of SPN was assessed.Results25,529 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 28 publications
3
24
2
1
Order By: Relevance
“…SPN of at least 5 mm size were found in 18% in the initial study collective. This ratio corresponds well to other published studies, which reported incidence rates ranging from 3.5% to 28% [9,[34][35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 92%
“…SPN of at least 5 mm size were found in 18% in the initial study collective. This ratio corresponds well to other published studies, which reported incidence rates ranging from 3.5% to 28% [9,[34][35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 92%
“…The baseline data were previously published [8] and show the prevalence of an SPN in the 25,529 consecutive patients included. Here we present the follow-up of 893 patients with SPN and of 15,185 patients without SPN (Fig.…”
Section: Patientsmentioning
confidence: 99%
“…Our group performed a multicentre cohort study in which we showed in the baseline data [8] the prevalence and associated characteristics of SPN in a general clinical population undergoing chest imaging (chest radiograph and CT). According to these results, the prevalence of SPN was lower than seen in previous screening studies [9]; hence, the probability of cancer and the variables associated in this population could also be different.…”
Section: Introductionmentioning
confidence: 99%
“…An indeterminate pulmonary nodule is a pulmonary lesion < 3cm found radiographically that does not have a tissue diagnosis. 15 They are found in 17-51% of chest CT scans and a conservative extrapolation suggests that at least 2 million indeterminate nodules are found annually 15,16 with a 1-12% chance of malignancy. 17 These symptomatic or incidentally discovered lung nodules represent a significant existing diagnostic burden.…”
Section: Indeterminate Pulmonary Nodulesmentioning
confidence: 99%